Mechanical and physical properties of inorganic polymer cement made of iron-rich laterite and lateritic clay: A comparative study. (February 2021) - Kaze, Cyriaque Rodrigue; Lecomte-Nana, Gisèle Laure; Kamseu, Elie; Camacho, Paula Sanz; Yorkshire, Antonia S.; Provis, John L.; Duttine, Mathieu; Wattiaux, Alain; Melo, Uphie Chinje
Abstract: In this work, two different laterites (iron contents of 13.07 and 49.34 wt%, respectively, for lateritic clay, LAC, and iron-rich laterite, LAI) were selected and calcined at 600 °C. The obtained calcined laterites, namely LAI600 and LAC600, were separately mixed with an alkaline solution (silicate modulus of 1.35) or an acidic solution (phosphoric acid solution at pH ≤ 2) for the synthesis of inorganic polymer products. The fabricated products were cured at 20 °C (ambient) and 40 °C (oven). The obtained results showed that the compressive strength of each series of alkaline-based inorganic polymer binder increased with ageing time (7 and 28 days) for room temperature curing, while the reverse trend was noted for oven-cured specimens. The best mechanical performance was obtained when using a phosphoric acid solution, 38 and 52 ± 1 MPa; 62 and 65 ± 1 MPa at 28 days for LAC and LAI respectively. It appeared that a higher iron content within the laterite contributed to an increase in the compressive strength under acidic conditions (LAI (59 MPa) > LAC (48 MPa)) compared to the behavior obtained under alkaline conditions (LAI (6 MPa) < LAC (29 MPa)). Accordingly, the acidic products exhibited a dense structure (with lower porosity) and contained amorphous iron/aluminium phosphate phases such as berlinite (FePO4 ), iron hydrogen phosphate hydrate (Fe3 H15 (PO4 )8· 4H2 O), ferrowyllieite (AlFe2 Na2 (PO4 )3 ) and sodium iron phosphate (Na3 Fe2 (PO4 )3 ) arising from the alteration of iron minerals in an acidic medium, confirmed by Mössbauer spectroscopy and electron paramagnetic resonance spectroscopy.